Аленушкины сказки: (6+) / Д. Н. Мамин-Сибиряк - Мамин-Сибиряк Дмитрий Наркисович (Любимые сказки малышам, 2014)
Экземпляры: ф.4 (20151015) / Инвентарный номер: 059524 / Цена: 145.00 / Авт.знак: М 22 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1